VesEcho Training System: Suprapubic Catheterization under Ultrasound Guidance. Issue 1 (January 2018) - Palvolgyi, Roland; Lee, Aaron; Ramirez, Francisco; Durbin‐Johnson, Blythe; Rothschild, Jennifer; Yang, Jennifer
Abstract : Introduction: : Suprapubic catheterization is a fundamental skill for urology residents and trainees. Ultrasound guidance for this procedure is effective for minimizing complications and the British Association of Urological Surgeons guideline recommends use of ultrasound for suprapubic catheterization whenever possible. We developed a novel, cost‐effective and sonographically accurate training model for suprapubic catheterization and incorporated it into our resident training curriculum. Methods: : The model consists of the 4 components of the bladder (water balloon), a pelvic bone replica and rectus fascia (nonrebreather masks), all housed within an ultrasound compatible gelatin mold. The model was tested during a resident training course to facilitate instruction of suprapubic catheterization. Surveys were administered before and after training to 13 participating urology residents, assessing the model's anatomical and sonographic realism as well as the utility of the curriculum in their education. Results: : The simulator model received a mean score of 4.2 out of 5 (SD 0.6, range 3 to 5) for anatomical realism and 4.4 out of 5 for sonographic realism (SD 0.5, range 4 to 5). The value of the simulator as a training tool was rated 4.7 and the overall value of the training course was rated 5 of 5. Regarding change in overall comfort with the procedure, mean total scores (out of 25) significantly increased for all residents after the training course (14.6 to 19.7, 5.1‐point increase, p <0.001). Conclusions: : Our novel simulation model and didactic curriculum received positive evaluations from urology residents and increased their comfort with ultrasound guided suprapubic catheterization. It is a sustainable teaching tool and can easily be incorporated into any urology training curriculum.